2010
DOI: 10.1143/jjap.49.106502
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hierarchically Micro- and Nano-structured Mold Surfaces Using Laser Ablation for Mass Production of Superhydrophobic Surfaces

Abstract: Many studies have examined the formation of surfaces with mixed patterns of micro- and nano-sized lotus leaves that have hydrophobic properties. In this study, micro- and nano-shapes such as lotus leaves were fabricated on a metal mold surface using laser ablation and ripple formation. A microstructure on the mold surface was replicated onto poly(dimethylsiloxane) (PDMS) using the polymer casting method to manufacture low-cost hydrophobic surfaces. A PDMS surface with micro- and nano-structures that were the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…The theoretical beam diameter of a laser beam after passing through the focusing lens is calculated by the following equation [74,75]:…”
Section: Experimental Procedures and Parametersmentioning
confidence: 99%
“…The theoretical beam diameter of a laser beam after passing through the focusing lens is calculated by the following equation [74,75]:…”
Section: Experimental Procedures and Parametersmentioning
confidence: 99%
“…On the other hand, laserinduced surface structures that are formed under laser irradiation have feature sizes smaller than the effective beam diameter, and the latter has been the subject of extensive research in recent years. Laser-induced structures that have been discovered on metals include laser-induced periodic surface structures (LIPSS) [4][5][6], bumps/cones [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], holes [7,9,17,18,23], undulating grooves [7,9,17], melt-like [18,24], and chaotic structures [7,9,25]. These laser-induced structures can be used to alter the wettability of a material, resulting in a more hydrophobic or hydrophilic surface [10,11,26].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that when an irradiated area is rescanned multiple times at a particular experimental setting, the surface features become increasingly regular and well-defined. Similarly, Noh et al [13] fabricated highly regular arrays of bumps and pillars on NAK80 mold steel by repeating their laser scan thirty and fifty times, respectively. Kam et al [11] observed the formation of two distinct types of micro-cones on stainless steel 316L, which only appeared after the target was scanned more than one hundred times.…”
Section: Introductionmentioning
confidence: 99%
“…Lasers with pulse durations ranging from a few picoseconds to femtosecond are currently under development; these lasers are referred to as ultra-short pulse lasers, and research using these lasers for laser ablation drilling has been conducted [12][13][14][15][16][17][18]. By using these lasers, the heataffected zone inevitably created during laser ablation can be reduced [19,20]. In TSV technology, it is crucial to minimize the heat-affected zone around the holes since the small cracks generated from this zone become larger, eventually damaging the circuit board [21].…”
Section: Introductionmentioning
confidence: 99%